Contribution of Eat1 and Other Alcohol Acyltransferases to Ester Production in Saccharomyces cerevisiae - Kruis, Aleksander J.; Gallone, Brigida; Jonker, Timo; Mars, Astrid E.; van Rijswijck, Irma M. H.; Wolkers–Rooijackers, Judith C. M.; Smid, Eddy J.; Steensels, Jan; Verstrepen, Kevin J.; Kengen, Servé W. M.; van der Oost, John; Weusthuis, Ruud A. (Frontiers in Microbiology, 2018)
Esters are essential for the flavour and aroma of fermented products, and are mainly produced by alcohol acyl transferases (AATs). A recently discovered AAT family named Eat (Ethanol acetyltransferase) contributes to ethyl acetate synthesis in yeast. However, its effect on the synthesis of other esters is unknown. In this study, the role of the Eat family in ester synthesis was compared to that of other S. cerevisiae AATs (Atf1, Atf2, Eht1, and Eeb1) in silico and in vivo. A genomic study in a collection of industrial S. cerevisiae strains showed that variation of the primary sequence of the AATs did not correlate with ester production. Fifteen members of the eat family from nine yeast species were overexpressed in S. cerevisiae CEN.PK2-1D and were able to increase the production of acetate and propanoate esters. The role of Eat1 was then studied in more detail in S. cerevisiae CEN.PK2-1D by deleting eat1 in various combinations with other known S. cerevisiae AATs. Between 6 and 11 esters were produced under three cultivation conditions. Contrary to our expectations, a strain where all known AATs were disrupted could still produce e.g. ethyl acetate and isoamyl acetate. This study has expanded our understanding of ester synthesis in yeast but also showed that some unknown ester-producing mechanisms still exist.